Probiotic Supplements Accelerate Bone Repair and Prevent Systemic Bone Loss Following Femoral Fracture (FS09-04-19). (24th October 2019) - Roberts, Joseph; Darby, Trevor; Fernandes, Lorenzo; Jones, Rheinallt; Drissi, Hicham
Abstract: Objectives: Fracture is a traumatic event that can initiate systemic bone loss and lead to increased future risk of fracture, especially in the elderly. We sought to determine whether modulation of the gut microbiome using a daily probiotic supplement would dampen systemic inflammatory responses to fracture to accelerate bone repair and preserve distant bone sites. Methods: Twelve-week-old male C57BL/6 J mice were randomly assigned to receive the probiotic Bifidobacterium adolescentis (1 × 10 8 CFU) via a daily oral gavage or PBS vehicle control. After two weeks, experimental mid-diaphyseal femoral fractures were created. Bones were analyzed using micro-CT at 10 and 18-days post-fracture. Midsagittal histological sections of fractured femora were stained with TRAP to quantify osteoclast number within the callus. RNA isolated from the small intestines was analyzed for gene expression of tight junction proteins. Serum levels of 20 cytokines were measured and analyzed using principal components analysis (PCA). Results: Micro-CT of fractured limbs revealed a significant increase in callus bone volume (+28%) at day 18 post-fracture in mice receiving the B. adolescentis supplement. The total number of osteoclasts within the fracture callus at day 18 was also significantly increased (+158%) in the probiotic group suggesting more advanced remodeling of the callus. Micro-CT analyses of the L3 vertebral body, a distant bone site, revealed significantly higher trabecular bone volume at day 10 (+ 22%) and 18 (+11%) post-fracture in the probiotic group. PCA of serum cytokines revealed distinct clustering of the B. adolescentis and PBS groups indicating an anti-inflammatory effect by B. adolescentis . In the small intestines, probiotic supplementation significantly increased gene expression of tight junction proteins occludin, Jam3, ZO-1, and claudin-15 at both day 10 and day 18 post-fracture. Conclusions: Daily B. adolescentis supplementation not only accelerated fracture healing but also protected against vertebral body bone loss following fracture. These effects are likely a consequence of tightened intestinal barrier integrity, thus preventing systemic inflammation stemming from fracture-induced gut permeability. Funding Sources: Funding provided by Emory University and the Burroughs Wellcome Fund.